Host–parasite relatedness shown by protein fingerprinting in a brood parasitic bird - Andersson, Malte (The National Academy of Sciences, 2000)
Brood parasitism as an alternative female breeding tactic is particularly common in ducks, where hosts often receive eggs laid by parasitic females of the same species and raise their offspring. Herein, we test several aspects of a kin selection explanation for this phenomenon in goldeneye ducks (Bucephala clangula) by using techniques of egg albumen sampling and statistical bandsharing analysis based on resampling. We find that host and primary parasite are indeed often related, with mean r = 0.13, about as high as between first cousins. Relatedness to the host is higher in nests where a parasite lays several eggs than in those where she lays only one. Returning young females parasitize their birth nestmates (social mothers or sisters, which are usually also their genetic mothers and sisters) more often than expected by chance. Such adult relatives are also observed together in the field more often than expected and for longer periods than other females. Relatedness and kin discrimination, which can be achieved by recognition of birth nestmates, therefore play a role in these tactics and probably influence their success.